2020
DOI: 10.1016/j.molcel.2019.12.007
|View full text |Cite
|
Sign up to set email alerts
|

The Aspartic Protease Ddi1 Contributes to DNA-Protein Crosslink Repair in Yeast

Abstract: Naturally occurring or drug-induced DNA-protein crosslinks (DPCs) interfere with key DNA transactions if not timely repaired. The unique family of DPC-specific proteases Wss1/SPRTN targets DPC protein moieties for degradation, including topoisomerase-1 trapped in covalent crosslinks (Top1ccs). Here we describe that the efficient DPC disassembly requires Ddi1, another conserved predicted protease in Saccharomyces cerevisiae. We found Ddi1 in a genetic screen of the tdp1wss1 mutant defective in Top1cc processing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
95
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(103 citation statements)
references
References 77 publications
8
95
0
Order By: Relevance
“…Our results imply that non-viral retroviral-like PRs potentially have relatively lower dimer stability compared to retroviral counterparts. We assume that getting better insight into the structural requirements for the dimer formation through the protease domain may help understanding the roles of Ddi-like proteins in proteasomal shuttles and ubiquitination pathways [6,7,63,64,67,68,84,85], even in physiological or pathological conditions. Furthermore, future studies are needed to prove our findings by determining the in vitro dimer stabilities, and correlating the features described in our study with those of additional eukaryotic retroviral-like or endogenous retrovirus PRs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results imply that non-viral retroviral-like PRs potentially have relatively lower dimer stability compared to retroviral counterparts. We assume that getting better insight into the structural requirements for the dimer formation through the protease domain may help understanding the roles of Ddi-like proteins in proteasomal shuttles and ubiquitination pathways [6,7,63,64,67,68,84,85], even in physiological or pathological conditions. Furthermore, future studies are needed to prove our findings by determining the in vitro dimer stabilities, and correlating the features described in our study with those of additional eukaryotic retroviral-like or endogenous retrovirus PRs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on wild-type and active site mutant Ddi1-Lm proteins revealed changes of the secretion phenotype, and their sensitivity to HIV PR inhibitors also implied the existence of catalytic activity [60]. Studies on Ddi1-Sc PR provided evidence for its proteolytic activity, which was found to be required for sufficient checkpoint regulation [61] and to contribute to protein secretion [62], DNA replication stress response [63], and DNA-protein crosslink repair [64]. In Caenorhabditis elegans, Ddi1 expression was found to be induced by proteasome dysfunction; furthermore, results proved that the catalytic activity of Ddi1 PR is necessary for protein activation [65], and involvement of PR activity in Nrf1 processing was also demonstrated for human Ddi2 PR [66,67].…”
Section: Introductionmentioning
confidence: 99%
“…vesicle fusion with the plasma membrane (22)(23)(24)(25). Recent reports show that, along with the metalloprotease Wss1, Ddi1 is involved in the disassembly of DNA-protein cross-links (26,27). Ddi1's putative target in this pathway is the core component of stalled RNA polymerase II (27).…”
Section: Significancementioning
confidence: 99%
“…In addition, Rad53 mediates a phosphorylation-dependent degradation of excess histones, and this mechanism is also likely to function during replication stress (Gunjan and Verreault, 2003;Singh et al, 2009). More recently, Ddi1 was implicated to function in parallel to Wss1 for providing replication stress tolerance (Serbyn et al, 2020;Svoboda et al, 2019). Cells use multiple pathways to counteract excess histones during replication stress.…”
Section: Discussionmentioning
confidence: 99%